Cobalt-modified covalent organic framework as a robust wateroxidation electrocatalyst - Aiyappa, Harshitha Barike; Thote, Jayshri; Shinde, Digambar Balaji; Banerjee, Rahul; Kurungot, Sreekumar (Chemistry of Materials, 2016)
The development of stable, efficient oxygen evolution reaction (OER) catalyst capable of oxidizing water is one of the premier challenges in the conversion of solar energy to electrical energy, because of its poor kinetics. Herein, a bipyridine-containing covalent organic framework (TpBpy) is utilized as an OER catalyst by way of engineering active Co(II) ions into its porous framework. The as-obtained Co-TpBpy retains a highly accessible surface area (450 m(2)/g) with exceptional stability, even after 1000 cycles and 24 h of OER activity in phosphate buffer under neutral pH conditions with an overpotential of 400 mV at a current density of 1 mA/cm(2). The unusual catalytic stability of Co-TpBpy arises from the synergetic effect of the inherent porosity and presence of coordinating units in the COF skeleton.

Constructing covalent organic frameworks in water via dynamic covalent bonding - Thote, Jayshri; Aiyappa, Harshitha Barike; Kumar, Raya Rahul; Kandambeth, Sharath; Biswal, Bishnu P.; Shinde, Digambar Balaji; Roy, Neha Chaki; Banerjee, Rahul (Iucrj, 2016)
The formation of keto-enamine based crystalline, porous polymers in water is investigated for the first time. Facile access to the Schiff base reaction in water has been exploited to synthesize stable porous structures using the principles of Dynamic Covalent Chemistry (DCC). Most credibly, the water-based Covalent Organic Frameworks (COFs) possess chemical as well as physical properties such as crystallinity, surface area and porosity, which is comparable to their solvothermal counterparts. The formation of COFs in water is further investigated by understanding the nature of the monomers formed using hydroxy and non-hydroxy analogues of the aldehyde. This synthetic route paves a new way to synthesize COFs using a viable, greener route by utilization of the DCC principles in conjunction with the keto-enol tautomerism to synthesize useful, stable and porous COFs in water.